1996
DOI: 10.1101/gr.6.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel human gene related to vascular endothelial growth factor.

Abstract: This paper describes the cloning and characterization of a new member of the vascular endothelial growth factor (VEGF) gene family, which we have designated VRF for VEGF-related-factor. Sequencing of cDNAs from a human fetal brain library and RT-PCR products from nor-mal and tumor tissue cDNA pools indicate two alternatively spliced messages with open reading frames of 621 and 564 bp, respectively. The predicted proteins differ at their carboxyl ends resulting from a shift in the open reading frame. Both isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 32 publications
(36 reference statements)
3
62
0
Order By: Relevance
“…Originally identified as a secreted product of tumour cells (Senger et al, 1983(Senger et al, , 1986, it is now apparent that VEGF is part of an emerging group of related molecules having approximately 15-25% homology at the amino acid level with the platelet-derived growth factor family. Other recently identified members include VEGF-related factor (VRF) or VEGF-B, VEGFReceived 27 November 1996 Revised 5 August 1997 Accepted 5 August 1997 Correspondence to: RE Banks C (Grimmond et al, 1996;Joukov et al, 1996;Olofsson et al, 1996;Paavonen et al, 1996) and placenta growth factor (Maglione et al, 1991;Hauser and Weich, 1993;Maglione et al, 1993). The active form of VEGF is a homodimeric cytokine of molecular weight 34-46 kDa, the variation in size being due to alternative exon splicing producing four different isoforms of 121, 165, 189 and 206 amino acids (monomeric size), the last three of which have heparin binding activity (Houck et al, 1991;Tischer et al, 1991).…”
mentioning
confidence: 99%
“…Originally identified as a secreted product of tumour cells (Senger et al, 1983(Senger et al, , 1986, it is now apparent that VEGF is part of an emerging group of related molecules having approximately 15-25% homology at the amino acid level with the platelet-derived growth factor family. Other recently identified members include VEGF-related factor (VRF) or VEGF-B, VEGFReceived 27 November 1996 Revised 5 August 1997 Accepted 5 August 1997 Correspondence to: RE Banks C (Grimmond et al, 1996;Joukov et al, 1996;Olofsson et al, 1996;Paavonen et al, 1996) and placenta growth factor (Maglione et al, 1991;Hauser and Weich, 1993;Maglione et al, 1993). The active form of VEGF is a homodimeric cytokine of molecular weight 34-46 kDa, the variation in size being due to alternative exon splicing producing four different isoforms of 121, 165, 189 and 206 amino acids (monomeric size), the last three of which have heparin binding activity (Houck et al, 1991;Tischer et al, 1991).…”
mentioning
confidence: 99%
“…Among the many reported angiogenic factors, vascular endothelial growth factor (VEGF) is the most powerful endothelial cellspecific mitogen associated with tumour neovascularization. While a number of investigators have reported the direct relationship between microvessel density (VD) and VEGF expression within a variety of tumours (Toi et al, 1994;Mattern et al, 1995;Samoto et al, 1995;Takahashi et al, 1995), recent studies also suggest that VEGF type B, C, D and E are novel regulators of endothelial cell proliferation (Grimmond et al, 1996;Joukov et al, 1996;Lee et al, 1996;Olofsson et al, 1996;Yamada et al, 1997;Meyer et al, 1999). Interestingly, the function of VEGF-C appears to extend to the lymphatic system where it serves as a ligand for fms-like tyrosine kinase 4 (flt-4) Jeltsch et al, 1997).…”
mentioning
confidence: 99%
“…5,6 VEGF 165 is half secreted and half bound to the cell surface and the extracellular matrix. 6 Over the past few years, four VEGF-related genes have been identified: VEGF-B, 7,8 VEGF-C, 9 VEGF-D, 10 VEGF-E 11 and placenta growth factor. 12 VEGF stimulates endothelial cell proliferation through binding to two related tyrosine kinase receptors, flt-1 and flk-1, on the surface of endothelial cells.…”
mentioning
confidence: 99%